1984
DOI: 10.1073/pnas.81.8.2295
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of cDNA for rat spleen thymosin beta 4.

Abstract: Molecular cloning of a cDNA has established the sequence of the translated portion of the mRNA for rat spleen thymosin beta 4. The presence of a methionyl initiator codon immediately preceding the codon for the first seryl residue of mature thymosin beta 4 is consistent with previous results indicating the absence of a signal peptide in the product translated in vitro from rat spleen mRNA. The cDNA sequence analysis also established the presence of two terminator codons immediately following the codon for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
1
18
0
2
Order By: Relevance
“…By this approach, 9 of the 10 clones showed no significant homologies to known sequences. However, clone 21b was found to be highly homologous to thymosin P34, a peptide with a wide tissue distribution (23,69). Clone 21b includes the entire coding region of thymosin 134, has an additional 21 bp at the 5' end, and extends to nucleotide 419 of the 523-bp published cDNA sequence (23) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By this approach, 9 of the 10 clones showed no significant homologies to known sequences. However, clone 21b was found to be highly homologous to thymosin P34, a peptide with a wide tissue distribution (23,69). Clone 21b includes the entire coding region of thymosin 134, has an additional 21 bp at the 5' end, and extends to nucleotide 419 of the 523-bp published cDNA sequence (23) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thymosin 4 mRNA is induced by alpha interferon in a human neuroblastoma cell line (21) and a lymphoblastoid cell line (49). Wodnar-Filipowicz et al (69) have hypothesized that thymosin N may be a component of the cytoskeleton. While such a role for thymosin 4 iS intriguing given the extensive morphological changes involved in PC12 neuronal differentiation and the induction of this mRNA by NGF, the precise physiologic role of thymosin 4 in NGF-responsive as well as in other cell types remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous Tb4 is known to be enzymatically acetylated in the cytosol. 34 The results showed that this PTM occurs in 293F cells.…”
Section: Membrane Permeabilizationmentioning
confidence: 92%
“…1 Three of the 16 purified cDNA sequences appeared identical to previously characterized genes that were not known to be expressed in pre-B-cells. The most highly represented sequence (designated PB37) among the original 97 phage clones corresponded to the previously defined gene for thymosin (34), a small secreted protein of unknown function. The PB17 sequence, which was represented once, corresponded to the gene for type II carbonic anhydrase (35).…”
Section: Resultsmentioning
confidence: 99%